Contribution of natural food to the growth and survival of tiger prawn postlarvae/Juveniles in brackishwater ponds - Gonzales, Eden P.; Machintosh, Donald J.; Lin, Chang Kwei; Wee, Kok Leong; DAAD - Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1988)
The relative contribution of natural food organisms present in a typical brackishwater prawn culture pond system to the growth and survival of Penaeus monodon postlarvae and juveniles was estimated using the food conversion ratio C FCR> as an index of nutritional efficiency. Twenty- day old postlarvae of weight 1 8 mg and length 11 . 4 mm were reared in 0. 15 - cm mesh, 3 m x 1 m x 1 . 75 m nylon net cages installed in an intensive commercial prawn grow out pond. Th e cages were either open to the bottom to allow the prawns access to benthic food organisms, or were suspended off bottom to prevent access to this food source . In two of the treatments, prawns were given commercial feed equivalent to 10% of their body weight. Natural food constituted about 5 1 % to 89% of the total food intake of the prawns during the two month s experimental culture period Con the assumption that the feeding efficiency of the prawns was 1 00%>. At the end of the c ultu re period, the prawns that received supplementary feed both in the cages that allowed access to benthos and those that did not, were significantly C P<O. 0 5) larger and heavier reaching 77. 1 mm; 3. 65 g and 78. 4 mm; 3. 87 g compared to 67. 6 mm; 2 . 37 g and 66. 7 mm; 2. 33 g for unfed prawns in equivalent cages. Th e natural food appeared to be sufficient for the prawns' nutritional needs for the first five to six weeks of culture until the supplementary feed became more important . This may have been because of the following factors: a) the natural food items in the pond became depleted by the prawns' grazing activities, b> plankton and other food organisms were dilute d during water exchanges which start e d from the fifth week of the culture period, and c)c hanging food habits or food preferences of t h e prawns as they grew larger.
A Thesis submitted in partial fulfilment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Shrimp culture